Istihsan in Determination of the Lunar Month: Jurisprudential Flexibility for Harmonizing the Ummah - Ananda Sy, Geubrina Rizky; Qiromi, Nur Mahmudi; Mahsun, Mahsun; Tajrid, Amir (Sinthop: Media Kajian Pendidikan, Agama, Sosial dan Budaya, 2025)
This article examines the role of Istihsan as a method of Islamic jurisprudential flexibility in determining Islamic law, particularly regarding the beginning of the lunar month, and reviews the positions of the four prominent schools of jurisprudence (Hanafi, Maliki, Hanbali, and Shafi'i) toward its application. Istihsan, which etymologically means "considering something better," remains a debated method of ijtihad among Islamic jurisprudence scholars (ushuliyyin), although still practically utilized. This study aims to explore how Istihsan functions as a jurisprudential catalyst in the application of astronomical science (Ilmu Falak), especially concerning the determination of lunar months, offering potential solutions for harmonizing differences among the Muslim community. Employing descriptive qualitative methods, the study uses primary sources from fiqh documentation related to Istihsan and astronomy, supplemented by secondary literature. The findings indicate that the Hanafi, Maliki, and some Hanbali scholars accept Istihsan with varying definitions and practical implementations. In contrast, the Shafi'i school rejects Istihsan, considering it as a form of subjective ijtihad lacking strong scriptural justification. Nevertheless, Istihsan serves as a foundation for jurisprudential flexibility, enabling Islamic law to effectively respond to contemporary challenges. Specifically, Istihsan acts as a bridge between the hisab (astronomical calculations) and rukyat (direct lunar observation) methods. It provides adaptive and maslahah-oriented solutions, such as prioritizing hisab in cases of doubtful rukyat, or vice versa, prioritizing rukyat to maintain unity within the community. Practically, Istihsan is exemplified through the Indonesian government's isbat sessions, which require integrated collaboration among scholars, astronomers, and government institutions, always maintaining compliance with definitive (qath'i) texts and public welfare (maslahah mursalah).